Health-related Quality of Life and Determinants of the Mental Dimension Among Tunisian Nurses in Public Hospitals - Bouzgarrou, Lamia; Merchaoui, Irtyah; Omrane, Amira; Ameur, Nada; Kammoun, Salma; Chaari, Neila (La Medicina del Lavoro, 2023)
Background: The health-related quality of life (HR-QoL) has been increasingly investigated in health sciences. The Objectives of this study are to evaluate the HR-QoL among nurses in Tunisian public hospitals and to identify the determinants of its mental dimension. Methods: A cross-sectional, bi-centric study was conducted within a representative sample of the 1,179 nurses assigned to 28 departments of two Tunisian public hospitals. A structured inquiry (socio-professional characteristics, occupational perceived workload) and validated questionnaires (SF12, Job Content Questionnaire of Karasek, Work Ability Index) have been completed. Results: Response rate was equal to 97.34%. The mean age of nurses was 42.60 ± 21 years. Nearly half of caregivers (49.07%) had a poor mental quality of life. The multivariate analysis concluded that mental HR-QoL was correlated with the female gender (0.010), obesity and the non-practice of regular physical activity (0.027), musculoskeletal diseases (<10-3), the low ability to work (<10-3). This deterioration of the mental HR-QoL dimension was also associated with the job tenure (0.002), the perceived workload (0.015), and conflictual relationships with colleagues (0.006) the feeling of insecurity at work (0.034), and the intention to leave the profession early (0.007) Conclusion: The results of this study showed that a considerable number of nurses had a poor mental quality of life. This study also identified factors associated with this deterioration. Acting on these determining factors may improve the well-being and global health of nurses, as well as their work performance and quality of care provided.